Land use/land cover change and its impact on ecosystem carbon storage in coastal areas of China from 1980 to 2050. (September 2022) - Zhu, Liya; Song, Ruixiang; Sun, Shuang; Li, Yang; Hu, Ke
Graphical abstract: Highlights: Past LULC changes can be divided into two stages: (I) accelerated evolution stage (1980–2010), and (II) stable evolution stage (2010–2020). Carbon storage presented a high-low-high distribution pattern from north to south. Areas with a rapid urbanization process exhibited more obvious changes in carbon storage dynamics. Rapid LULC dynamics have reduced the carbon sequestration capacity of the ecosystem. The implementation of ecological conservation could increase the carbon fixation in ecosystems. Abstract: Land use/land cover (LULC) change has greatly altered ecosystem carbon storage capacity and can eventually profoundly impact global climate change. Characterizing the LULC change and its impact on ecosystem carbon storage in coastal areas is greatly significant to comprehensively understanding the influences of human activities on ecosystems. Based on LULC data, this paper combined CA-Markov and InVEST models to evaluate the past, present, and future LULC change and its impact on ecosystem carbon storage in coastal areas of China. The results showed that past LULC change in coastal areas can be divided into two stages: (I) accelerated evolution stage (1980–2010), and (II) stable evolution stage (2010–2020). Changes in LULC types have led to a downward trend in ecosystem carbon storage, with a cumulative loss of 0.39 Pg and 0.15 Pg during the two stages, respectively. Spatially, carbon storage presented a high-low-high spatial distribution pattern from north to south. Temporally, areas with a rapid urbanization process exhibited more obvious changes in carbon storage dynamics. Compared with the natural change scenario, the areas with LULC types conversion under the ecological conservation scenario in 2050 will be lower due to the limitation of ecological protection, and it caused carbon storage reduction will slow down. Rapid LULC dynamics, that a large area of farmland, unused land and, water have been converted into construction land, reduced the carbon sequestration capacity of the ecosystem. This study will provide reliable references and precise data support for coastal management and decision-making.